Penggunaan Model Student Team Achiement Divisions (STAD) Dalam Meningkatkan Hasil Belajar Siswa (Penelitian Pada Mata Pelajaran Biologi Kelas XI IPA Pokok Bahasan Sistem Ekresi di SMA Negeri 27 Bandung Tahun Pelajaran 2018-2019) - Sarip Rustandi (Jurnal Ilmu Pendidikan dan Sosial, 2022)
The low learning outcomes of students in biology class XI science, the subject of the excretory system, is a problem that must be addressed immediately. The low learning outcomes are due to the low quality of learning in the classroom, including lack of motivation to learn, inappropriate learning models, incomplete infrastructure, and lack of opportunities for teachers to participate in training to improve teacher performance. This study aims to determine the application of the Student Team Achievement Division (STAD) learning model in improving student learning outcomes in Biology subjects in class XI IPA on the subject of the excretory system. The results showed that in the first action of the number of students as many as 36 people who got a score greater than or equal to the 2.67 KKM limit, as many as 11 students or 28.95% while in the second action the students who got a score above the KKM or 2 ,67 as many as 32 students or 84.21%. This means that there are significant differences in learning using the STAD method on student learning outcomes, so it can be concluded that learning using the STAD model can improve student learning outcomes in Biology subjects in class XI IPA, the subject of the excretory system.